Itinerários para a educação física escolar: explorando os museus de Belo Horizonte - Ana Cristina de Abreu Mazzoni (2020)
This paper discusses the importance of the relationship between museum, school and education for the student’s formation, since appropriating museum spaces can be a great opportunity to expand the repertoire of students and create a dialogue with the classroom. I mainly discuss how Physical Education can enter these spaces, creating possibilities outside the school walls. I emphasize during the research, that the knowledge to be shared in museums must be constructed, analyzed and contextualized, forming a network of meanings, in such a way that students can perceive and understand their pertinence. For this study, three museums in Belo Horizonte were chosen: Football Museum, Museum of Arts and Crafts and Museum of Toys. As a final product, a guide was created, with the title: “Itinerary for School Physical Education: Exploring the Museums of Belo Horizonte” with suggestive themes, related to the various body practices, to be worked on by teachers at school, at the museum and back to school.